Prevention of Iatrogenic Cervical Cancer*: A Critical Review - Klimek, Rudolf (Advancement and New Understanding in Medical Science Vol. 8, 2024)
Cervical carcinogenesis consists of natural occurring spontaneous cellular processes which may lead to self-organized dissipative structures of cervical cancers what was first explained in 1977. All the theories of carcinogenesis have properly described this event from methodologically different point of view. Man should understand the thermodynamic rules underlying each of these approaches. Neoplasms are self-organized from the cells of the patient, who did not provide the necessary conditions for cellular metabolism as defined in the moment of appearance of its zygote. In light of medical thermodynamics all oncogenic factors can divide into sufficient or necessary to events for creating a dissi-pathogenic cellular status. Cervical cancer is a tumor associated with the human papillomavirus as only its pathogenic dissi-pathogenic factors, but the genome of cervical carcinoma cells maybe the original source of many types of HPV from the peeled off cancer cells of the uterine cervix. Many things are known to increase the risk of carcinogenesis which as a natural process is an alternative of cellular or social death. Neoplasm cell is an effect of carcinogenesis, but not a causal point at which it begins its existence. Lastly M. Vopson suggests that information as the fundamental building block of the universe has physical mass and makes up almost a third of the universe, which he calls the mass-energy-information equivalence principle [82].The prolongation of invisible rays of information on the principle of just resonance creates an informational image of the original object without the participation of its atoms, confimed also at: 1. R Klimek (2015) Psychoneurocybernetic Conquest of Carcinogenesis and Cancers, Nova Biomedical., USA; 2. R Klimek (2019) Information Medicine-E=i mc2 WIU, ISBN 978-83- 923871-5-2, Cracow 2018 and BCnA 2019, 9: 369-492; 3.Klimek R, Tadeusiewicz R, Gralek P (2017) Virtual information links Matter and Energy: E=i mc2, in: Hisaki Hashi (ed.) Philosophy of Nature in Cross-Cultural Dimensions. Dr Kovac Publ., Hamburg.4. Klimek R (2016) Life, Cancer and Virtual Information, BCnA 6(2): 255- 272; 5. KS Khroutski, R Klimek (2018) Biocosmological definition of information and its naturalist causal significance. BCnA 8(2): 204-262 [77] - [81].